John Foster and the Integration of Faith and Learning - Spence, Martin (Christian scholar's review, 2013)
The “integration of faith and learning” has become a touchstone of many Evangelical Protestant higher education institutions in recent decades. Martin Spence argues that modern Evangelical scholars and teachers have intellectual forbears who long ago raised similar questions about the relationship between faith and learning. The author introduces one such individual, the nineteenth-century British Baptist minister and essayist John Foster (1770–1843), and provides a commentary on Foster’s essay “On Some of the Causes by which Evangelical Religion has been Rendered Unacceptable to Persons of Cultivated Taste” (1805). This essay critiqued the anti-intellectualism of popular Evangelical piety and called for the creation of scholarship that operated within explicitly Christian paradigms. The author contends that Foster’s aspiration for the cultivation of learning, creativity, and cultural intelligence in the Evangelical community both challenges and encourages contemporary Christian educators.